Data analysis for metropolitan economic and logistics development. Issue 2 (April 2017) - Lan, Shulin; Yang, Chen; Huang, George Q.
Highlights: Quantitative examination of relations between metropolitan logistics and economy. Objective weight determination for indicators in the evaluation index systems. Regression analysis of the development of metropolitan logistics and economy. Correlation and regression analysis between economic forms and logistics subsystems. Abstract: Logistics industry is an integral sector encompassing transportation, warehousing, handling, circulation and processing, delivery and information technology. With the progress of economic globalization and integration, logistics industry has become a new momentum driving the fast development of national and regional economy. The close relationship between economic development and logistics advancement receives wide attention from the academia. However, current research on the coordination between economy and logistics mostly focuses on concept interpretation, and qualitative discussions. Very rarely do scholars conduct quantitative analysis on the coordination of metropolitan economy and logistics. To fill this gap, we first examine whether there exist interactions between metropolitan logistics and economy by building evaluation index systems for metropolitan logistics and economy. Then we introduce the entropy method and Granger causality test to evaluate and test the level of logistics and economic development in five cities: Beijing, Shanghai, Guangzhou, Chongqing, and Tianjin from 2009 to 2013. From the dimensions of regional economic investment, regional economic capacity and strength, we finally test the relationship between three economic subsystems and three logistics subsystems to further validate the relationship between metropolitan economy and logistics.